2009
DOI: 10.1075/aral.32.3.03kim
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Aviation english as a Lingua Franca

Abstract: Researchers exploring the use of language use in radiotelephony communication have tended to focus on the limitations of the non-native English user and the threats which their limited control of English may pose for aviation safety (e.g. Atsushi, 2003Atsushi, , 2004. Hence the recent International Civil Aviation Organization (ICAO) policy places the onus on non-native users to bring their English to an appropriate standard. The present paper argues that there is a need for a broader perspective on this issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…These are but several characteristics of an oral language that can affect the pilot's ability to accurately decode message streams and parse their contents into something comprehensible. Kim and Elder (2009), with the help of eight experienced Aviation professionals (five ATCOs and three pilots), analyze recorded discourse data from the main international airport in Korea, involving instances of communication which were considered non-routine, abnormal or emergency situations so that they could identify factors that may contribute to misunderstandings. Even though under-utilization of phraseology was one of the main factors in miscommunication, pronunciation issues were also cited.…”
Section: One Pilot Stated Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…These are but several characteristics of an oral language that can affect the pilot's ability to accurately decode message streams and parse their contents into something comprehensible. Kim and Elder (2009), with the help of eight experienced Aviation professionals (five ATCOs and three pilots), analyze recorded discourse data from the main international airport in Korea, involving instances of communication which were considered non-routine, abnormal or emergency situations so that they could identify factors that may contribute to misunderstandings. Even though under-utilization of phraseology was one of the main factors in miscommunication, pronunciation issues were also cited.…”
Section: One Pilot Stated Thatmentioning
confidence: 99%
“…Hancock (2018, p. 4) highlights that if students are aiming for intelligibility, the focus should be the essential features (phoneme distinctions, syllables and tonic stress); as they "are for the benefit of the listener -these features serve to make the intended communication clearer and less ambiguous." Kim and Elder (2009) point out:…”
Section: Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In spite of ICAO's efforts, the ability of pilots to use Aviation English is still questioned and has been the subject of a number of studies and reports (e.g. EUROCONTROL, 2006b;BILLINGTON, 2016;ELDER, 2009;TIEWTRAKUL;FLETCHER, 2010). Looking at commercial aviation, Tiewtrakul and Fletcher (2010) found that pilots failed to understand 79 out of 312 ATC messages at Bangkok International Airport, and that miscommunication between Thai ATC and non-native English speaking (NNES) foreign pilots was consistently higher than with Thai or native English speaking (NES) pilots.…”
Section: Introductionmentioning
confidence: 99%